Candidal liver abscesses and cholecystitis in a 37-year-old patient without underlying malignancy - Lai, Chung-Hsu (World J Gastroenterol, 2005)
We report a case of candidal liver abscesses and concomitant candidal cholecystitis in a diabetic patient, in whom differences were noted relative to those found in patients with hematologic malignancies. In our case, the proposed entry route of infection is ascending retrograde from the biliary tract. Bile and aspirated pus culture repeatedly tested positive, and blood negative, for Candida albicans and Candida glabrata. Cholecystitis was cured by percutaneous gallbladder drainage and amphotericin B therapy. The liver abscesses were successfully treated by a cumulative dosage of 750 mg amphotericin B. We conclude that in cases involving less immunocompromised patients and those without candidemia, a lower dosage of amphotericin B may be adequate in treating candidal liver abscesses.